SEE characterization and mitigation in ultra-deep submicron technologies - Mavis, D.G.; Eaton, P.H.; Sibley, M.D. (2009 IEEE International Conference on IC Design and Technology, 2009)
As technology feature sizes decrease, single event upset (SEU), digital single event transient (DSET), and multiple bit upset (MBU) effects dominate the radiation response of microcircuits in space applications. Even in high-altitude and terrestrial applications, cosmic-ray neutron recoil byproducts can easily produce an unacceptable soft error rate (SER) in modern microcircuits. Process modifications and engineered substrate attempts have not provided significant levels of SEE (single event effect) mitigation. Circuit-level hardening approaches have, however, proven effective in mitigating all heavy-ion related effects. The size and speed penalties associated with these circuit hardening techniques often cannot be tolerated in commercial product designs. For this reason, experimental SEE characterization is necessary to identify dominant response mechanisms so that critical circuits can be identified and hardened with minimal impact on overall IC performance and permit the most effective trade-off between SER and the area/speed overhead. For complex designs, conventional broad-beam testing provides limited data to isolate the exact cause of observed errors and little insight into potential design improvements. We report on our new Milli-Beamtrade test hardware and associated data acquisition software that provide rapid SER raster scanning with spatial isolation as small as 10 microns to physically isolate dominant circuit susceptibilities of complex modern microcircuits.